2010
DOI: 10.4155/bio.10.73
|View full text |Cite
|
Sign up to set email alerts
|

Performance Properties of Filter Paper Devices for Whole Blood Collection

Abstract: The data demonstrated similarities of analyte recovery between the papers, indicating comparability of the devices for newborn screening and other applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 14 publications
2
50
0
Order By: Relevance
“…These filter card systems are highly uniform and have very similar absorption characteristics so that analytical results obtained from capillary blood prepared on either of them do not differ by more than 4% -5% 28 . Not surprisingly, Masciotra and co-workers 29 therefore detected HIV-1 RNA equally well with a qualitative assay after elution from blood collection cards from different sources.…”
Section: Parametersmentioning
confidence: 99%
“…These filter card systems are highly uniform and have very similar absorption characteristics so that analytical results obtained from capillary blood prepared on either of them do not differ by more than 4% -5% 28 . Not surprisingly, Masciotra and co-workers 29 therefore detected HIV-1 RNA equally well with a qualitative assay after elution from blood collection cards from different sources.…”
Section: Parametersmentioning
confidence: 99%
“…We have developed a method using dried plasma or whole blood in filter paper [Aabye MG, Ruhwald M, Unpublished Data]. Biomarkers are stable in dried blood and plasma at ambient temperature [97], therefore the filter paper technology enables cheap and simple sample transport over long distances by normal mail, and centralized analysis vis à vis the neonatal screening for metabolic diseases [84].…”
Section: Reviewmentioning
confidence: 99%
“…The published acceptable serum-absorption volume per 1/8-inch disk punched from a 100 μL spot of intact-cell blood of 55% hematocrit is 1.54 ± 0.17 μL [4]. Furthermore, many other peer-reviewed reports have described the effects of hematocrit on quantitative measures from DBS [5], as well as differences between filter paper manufacturers obtained from careful study of different types of analytes in DBS [6]. The latter study's data indicated that the difference in analytical results between manufacturers could be at least 4-5% for comparability or, at a minimum, equal to the lotto-lot variance of a single manufacturer's filter paper products.…”
Section: Dried Blood Spots: Fifty Years Of Knowledge About the Filtermentioning
confidence: 99%